STUDI KUALITATIF: KEJADIAN INFEKSI BERULANG SARS-CoV-2 DI RUMAH SAKIT PUSAT ANGKATAN DARAT GATOT SOEBROTO PERIODE JANUARI-JULI 2022 - Monica Gres Mona Sinaga, (2023)
Background: Several cases of reinfection with SARS-CoV-2 have been reported worldwide. The first reported case of reinfection occurred 4.5 months (142 days) after the first episode of COVID-19 infection. This study aims to look at the proportion of patients who have recurrent infections and the description of patients with recurrent infections in terms of age, sex, location of residence, vaccination status, comorbidities, and degree of severity. Methods: This research is a qualitative descriptive study with a non-probability sampling technique used to search data using SIRS (Sistem Informasi Rumah Sakit). The variables studied were age, gender, location of residence, vaccination status, comorbidities, and severity in patients with recurrent COVID-19 infections. Results: This study showed that the proportion of patients with recurrent infections was 4.1%, with complete vaccination of 45.2% and incomplete vaccination of 54.8%. Elderly patients are susceptible to being infected with COVID-19 again with an age scale of 51-60 years. The difference in the proportions between men and women is not significant and Central Jakarta is the location of residence with the most frequent recurrent infections. The most common comorbidities experienced by patients are chronic kidney disease, essential (primary) hypertension, non-insulin-dependent diabetes mellitus. Patients with repeated infection with COVID-19 tend to experience symptoms of moderate severity. Conclusion: The variables that most influence the incidence of recurrent infections are age, co-morbidities and vaccination status and patients who experience recurrent infections with COVID-19 tend to experience clinical symptoms of moderate severity